GEN-Z PERSPECTIVE ON POLITICS: HIGH INTEREST, UNINFORMED, AND URGING POLITICAL EDUCATION - Patricia Robin; Silvanus Alvin; Tesalonika Hasugian (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2022)
The Central Bureau of Statistics report reveals that Gen-Z dominates Indonesia's population today. This data is necessary considering that in 2024 a general election will be held. The votes from gen-z will undoubtedly be a bone of contention for competing politicians and political parties. In political communication, research is often focused on strategies for compiling narratives that can be converted into vote gains or political image management to attract sympathy. These two things can only be done when they know the perspective of the target public. Therefore, this study aims to determine the perspective of Gen Z. This qualitative study uses the focus group discussion method to obtain in-depth data. There are three interesting findings: Gen-Z is highly interested in politics but feels uninformed. Second, Gen-Z sees the existence of political parties in a negative light due to the high number of corruption cases. Third, Gen-Z urges for political education. Each finding is elaborated on in this research paper.